Relations among perceived stress, fatigue, and sleepiness, and their effects on the ambulatory arterial stiffness index in medical staff: A cross-sectional study - Lang, Xiaorong; Wang, Quan; Huang, Sufang; Feng, Danni; Ding, Fengfei; Wang, Wei (Frontiers in Psychology, 2022)
Objective: To explore the relationship between perceived stress, fatigue and sleepiness and the pathway of their effects on ambulatory arterial stiffness index (AASI) of medical staffs. Methods: This was a cross-sectional study conducted in a tertiary hospital in Wuhan. Perceived stress, fatigue and sleepiness was measured using Perceived Stress Scale (PSS), Fatigue Assessment Scale (FAS), and Epworth Sleepiness Scale (ESS), respectively. AASI was obtained from 24-h ambulatory blood pressure monitoring recordings. Path analysis was used to clarify the relationship between PSS, FAS, ESS scores and AASI value. Results: A total of 153 participants were included in the study. PSS and FAS correlated with ESS (r=0.424 p<0.01), and PSS correlated with FAS (r=0.614, p<0.01). In addition, ESS correlated with AASI (r=0.225, p<0.01). According to the results of path analysis, PSS and FAS have no direct effect on AASI, but have indirect effect on AASI (β=0.059, 95% CI=0.017-0.126, p<0.01; β=0.059, 95%CI=0.016-0.136, p<0.01) by influencing ESS (β=0.263, β=0.262, p<0.01). Conclusion: Sleepiness was a mediator of the effects of perceived stress and fatigue on AASI.